Intra-articular delivery of a nanocomplex comprising salmon calcitonin, hyaluronic acid, and chitosan using an equine model of joint inflammation - Tajber, Lidia; Sladek, Svenja; Kearney, Clodagh; Crean, Daniel; Brama, Pieter A.J.; Fawcett, Karolina; Labberte, Margot C.; Leggett, Bernadette; Brayden, David J. (My University, 2018)
Polyelectrolyte nanoparticle constructs (NPs) comprising salmon calcitonin (sCT), chitosan (CS), and hyaluronic acid (HA) were previously established as having anti-inflammatory potential when injected via the intra-articular (i.a.) route to a mouse model. We attempted to translate the formulation to a large animal model, the lipopolysaccharide (LPS)-stimulated equine model of joint inflammation. The aim was to manufacture under aseptic conditions to produce sterile pyrogen-free NPs, to confirm physicochemical characteristics, and to test toxicity and efficacy in a pilot study. NP dispersions were successfully formulated using pharmaceutical-grade source materials and were aseptically manufactured under GMP-simulated conditions in a grade A modular aseptic processing workstation. The NP formulation had no detectable pathogen or endotoxin contamination. NPs were then tested versus a lactated Ringer’s solution control following single i.a. injections to the radiocarpal joints of two groups of four horses pre-treated with LPS, followed by arthrocentesis at set intervals over 1 week. There was no evidence of treatment-related toxicity over the period. While there were no differences between clinical read-outs of the NP and the control, two synovial fluid-derived biomarkers associated with cartilage turnover revealed a beneficial effect of NPs. In conclusion, NPs comprising well-known materials were manufactured for an equine i.a.-injectable pilot study and yielded no NP-attributable toxicity. Evidence of NP-associated benefit at the level of secondary endpoints was detected as a result of decreases in synovial fluid inflammatory biomarkers.
PUBLISHED
Keywords: Salmon calcitonin; Hylauronic acid; Chitosan; Joint inflammation; Synovitis; Nanomedicine; Large animal models; Immunology, Inflammation & Infection; Nanoscience & Materials; ANTI-INFLAMMATORY DRUGS; CHITOSAN; HYALURONATE; polyelectrolyte nanoparticles; salmon calcitonin